Recent Progress on the [3+2] Cycloaddition Route for the Synthesis of All-Carbon Quaternary Stereocentres - Deepthi, Ani; Mohan, Maneesh; Balachandran, Meenakshy C. (SynOpen, 2022)
Construction of all-carbon quaternary centres is an important task in organic synthesis. In spite of the challenges associated with Csp3–Csp3 bond construction in a sterically constrained environment, significant advances have been made in this area. Among the latter, both catalytic and noncatalytic [3+2] cycloaddition approaches have gained wide attention recently. This short review summarizes the [3+2] cycloaddition reactions reported during the period 2016–2022 for the synthesis of molecules possessing one or more all-carbon quaternary stereocentres.
Keywords: all-carbon; quaternary; stereocentres; [3+2] cycloaddition; cyclization